Pengembangan E-Modul Keanekaragaman Hayati Berbasis Penelitian Plankton di Perairan Estuari Kawasan Konservasi Mangrove Baros bagi Peserta Didik Kelas X SMA - Choirunnisa, Eyrin; Kurniawati, Atik (Jurnal Inovasi Pembelajaran Biologi, 2025)
This study aims to identify the types of plankton found in the estuarine waters of the Mangrove Baros Conservation Area and explore their potential as a learning resource for biology. Additionally, it seeks to analyze the validity and effectiveness of a research-based biology e-module on plankton in enhancing students' understanding. This research is an exploratory and development study (R&D) using the 4D development model (Define, Design, Develop, and Disseminate). Plankton data collection was carried out through sample observations, while the e-module assessment was conducted using questionnaires completed by material experts, media experts, teachers, and students. The study was conducted from September 2024 to February 2025. The research instruments included interview sheets, validation assessment questionnaires, and response questionnaires. The effectiveness of the e-module was analyzed using the N-Gain test. The results of the N-Gain test analysis indicate that the biology e-module based on plankton research is classified as moderately effective, with a score of 71.6%. Meanwhile, the validation results from material experts showed an e-module validity level of 99%, and media experts rated it at 89%, classifying it as highly valid. Thus, the biodiversity e-module based on plankton research in the estuarine waters of the Baros Mangrove Conservation Area can be used as a valid and moderately effective teaching material to enhance students' understanding.